176k views
4 votes
For the Dividend Growth Model, the equation can be written as follows: P0 = =D1/(RE – g). How can this equation be rearranged?

A) RE = D1/g + P0
B) RE = D1 * P0 + g
C) RE = D1/P0 + g
D) RE = g /P0 + D1
E) RE = P0/D1 + g

User Joette
by
4.9k points

1 Answer

2 votes

Answer:

C) RE = D1/P0 + g

Step-by-step explanation:

The formula above is the cost of retained earnings or the cost of equity.

The first portion of the formula (D1/P0) is known as dividend yield which is simply dividend divided by price.

The second part(g) is known as the growth rate of dividends.

The initial formula is rearranged thus:

P0=D1/(RE – g)

P0*(RE – g)=D1

RE – g=D1/P0

RE=D1/P0+g

User MacUsers
by
4.6k points